Survivorship and Patient-Reported Outcomes After Comprehensive Arthroscopic Management of Glenohumeral Osteoarthritis: Minimum 10-Year Follow-up. Issue 7 (30th July 2021) - Arner, Justin; Elrick, Bryant; Nolte, Philip; Horan, Marilee; Millett, Peter; Haber, Daniel
Objectives: Glenohumeral osteoarthritis (GHOA) remains a common cause of shoulder pain, loss of shoulder range of motion, and upper extremity dysfunction. Few long-term outcome studies exist evaluating glenohumeral osteoarthritis (GHOA) treatment with arthroscopic management. The purpose of this study was to determine outcomes, risk factors for failure, and survivorship for the comprehensive arthroscopic management (CAM) procedure for the treatment of GHOA at minimum 10-year follow-up. It was hypothesized that while some patients would progress to total shoulder arthroplasty (TSA), the majority of patients would demonstrate sustained improvement in patient-reported outcomes and satisfaction without conversion to TSA at long term follow-up. Methods: The CAM procedure was performed on a consecutive series of patients with advanced GHOA who opted for joint preservation surgery that otherwise met criteria for total shoulder arthroplasty (TSA). At minimum 10-year follow-up, pre- and post-operative outcome measures collected included the American Shoulder and Elbow Surgeons (ASES), Single Assessment Numeric Evaluation (SANE), Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH), Short Form–12 (SF-12) Physical Component Summary (PCS), visual analog scale for pain, and satisfaction scores. Kaplan-Meier survivorship analysis was performed with failure defined as progression to arthroplasty. Results: Thirty-eight CAM procedures were performed with 10-year minimum follow-up (range, 10-14 years) with a mean age of 53 years (range, 27-68) at time of surgery. Kaplan Meier survivorship curve showing 75.3% CAM survivorship (Comprehensive Arthroscopic Management) for glenohumeral arthritis at 5 years and 63.2% at 10 years in Figure 1. Those who progressed to arthroplasty did so at a mean of 4.7 years (range, 0.8-9.6 years). For those who did not undergo arthroplasty, ASES scores significantly improved post-operatively at both 5 and 10 years (63.3-89.6, p<0.001; 63.3-80.6, p=.007) (Table 1). CAM failure was associated with severe pre-operative humeral head incongruity in 93.8% of failures compared to 50.0.% of patients who did not go onto arthroplasty (p= 0.008). Median satisfaction was 7.5 out of 10. Conclusions: Significant improvement in patient reported outcomes were sustained at minimum 10-year follow-up in young patients with GHOA who underwent a CAM procedure. Survivorship rate at minimum 10-year follow-up was 63.2%. Humeral head flattening and severe joint incongruity were risk factors for CAM failure. The CAM procedure is an effective joint preserving treatment for GHOA in appropriately selected patients with sustained positive outcomes at 10 years. :